Comprehensive study on physicochemical properties of materials based on titanium suboxides - Velichenko, Alexander; Knysh, Valentina; Shmychkova, Olesia; Luk’yanenko, Tatiana; Pukas, Svitlana; Demchenko, Pavlo; Kordan, Vasyl; Gladyshevskii, Roman (Physics and Chemistry of Solid State, 2024)
This study focuses on the surface structures and microstructural changes of titanium dioxide nanotubes, when electrochemically coated with platinum and/or palladium. Ti samples anodized in a fluorine-containing electrolyte exhibit self-organized nanotubes of varying diameters with open pores. Annealing at 773 K led to compaction of the porous layer, the formation of cracks, and the appearance of corrugation in the nanotubes. The deposition of platinum produced a transition from a nanotubular surface structure to a microcrystalline structure consisting of rutile crystallites. The palladium-coated samples showed fused blocks characteristic of titanium suboxides. The tubular structure was preserved, even after crystallization. SEM images revealed a comb-like pattern in coatings with varying metal content. XRPD analysis confirmed the presence of anatase and elemental titanium. PdO was detected on the surface of the thermally treated samples. For samples co-treated with Pd and Pt, mutual diffusion of the two metals took place during the heat treatment. The findings reveal surface characteristics, metal deposition effects, and phase composition of titania nanotubes, providing valuable insights for further research.